1968
DOI: 10.1139/v68-349
|View full text |Cite
|
Sign up to set email alerts
|

Ion–molecule reactions in formic-d acid and methyl formate

Abstract: The following ion-molecules reactions have been found to occur in DCOOH for ions produced by bombardment with electrons of 10-15 eV energy (all rate constants in cm3 molecule-l units).[a] DC02H+ + DC0,H + DCO,HD+ + C0,H k = 1.0 x lo-,In methyl formate the following reactions have been identified and rate constants measured for ions formed by bombardment with electrons of 10-15 eV energy.[ f ] HC02CH3+ + HC02CH3 -. HC02CH3HC + ? k = 1.57 X lo-'Experiments using DCOzCH3 show that reaction [ f ] involves transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Although the protonation of CO 2 can occur at two different sites, an attachment of the proton to one of the oxygen atoms generates the more favorable that the hydroxycarbonyl cation (H ‐ O + ═ C ≡ O) . In fact, calculations have shown that the isomeric formyloxy cation (H–CO 2 + ) is about 90 kcal/mol less stable than the hydroxycarbonyl form . Our search by DFT calculations for energy‐minimized structures confirmed that the species which best represents the protonated CO 2 is that with the proton attached to one of the oxygen atoms of CO 2 (Fig.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Although the protonation of CO 2 can occur at two different sites, an attachment of the proton to one of the oxygen atoms generates the more favorable that the hydroxycarbonyl cation (H ‐ O + ═ C ≡ O) . In fact, calculations have shown that the isomeric formyloxy cation (H–CO 2 + ) is about 90 kcal/mol less stable than the hydroxycarbonyl form . Our search by DFT calculations for energy‐minimized structures confirmed that the species which best represents the protonated CO 2 is that with the proton attached to one of the oxygen atoms of CO 2 (Fig.…”
Section: Resultssupporting
confidence: 52%
“…We envisaged that the m/z 45 peak represents protonated carbon dioxide. Although the protonation of CO 2 can occur at two different sites, an attachment of the proton to one of the oxygen atoms generates the more favorable that the hydroxycarbonyl cation (H ‐ O + ═ C ≡ O) . In fact, calculations have shown that the isomeric formyloxy cation (H–CO 2 + ) is about 90 kcal/mol less stable than the hydroxycarbonyl form .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, protonated methyl formate can be produced through other reactions as outlined in the literature. This procedure involves a charge transfer to methyl formate from Ar + and Kr + , followed by a proton transfer with neutral methyl formate, i.e., HCO 2 CH 3 + + HCO 2 CH 3 HCO 2 CH 3 normalH + + CO 2 CH 3 goodbreak0em1em⁣ italick = 1.57 × 10 9 .25em cm 3 .25em molecule 1 …”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, protonated methyl formate can be produced through other reactions as outlined in the literature. This procedure involves a charge transfer to methyl formate from Ar + and Kr + , followed by a proton transfer with neutral methyl formate, 33 i.e.,…”
Section: ■ Experimental Sectionmentioning
confidence: 99%